THE INFLUENCE OF PRICE AND QUALITY OF SERVICE ON CUSTOMER SATISFACTION OF ONLINE TAXI TRANSPORTATION SERVICES (GRABCAR) - Dewi Nurmasari Pane (Universitas Negeri Medan, 2022)
The title of this research is